The cohesive parametric high-fidelity-generalized-method-of-cells micromechanical model. (1st December 2020) - Meshi, Ido; Breiman, Uri; Aboudi, Jacob; Haj-Ali, Rami
Abstract: The Parametric High-Fidelity-Generalized-Method-of-Cells (PHFGMC) micromechanical model is extended to include a local cohesive formulation for simulating discontinuities in multiphase composites. The nonlinear PHFGMC governing equations are obtained from a virtual work principle applied to both the local and far-field variables and solved using a new incremental-iterative formulation. The nonlinearity stems from the introduction of the cohesive zones in conjunction with damage evolution. The proposed formulation yields an overall symmetric system of equations and enables the implementation of advanced traction-separation laws available in the literature similar to the displacement-based finite element method (FEM). Two cohesive zone models are integrated with the PHFGMC with a unique nonlinear formulation. These are the non-potential based model proposed by Camanho and Davila (CD) and the potential based Park–Paulino–Roesler (PPR) model. This article presents comparisons with FEM and the applications of this modeling approach. The predictions of damage initiation and evolution, as well as the overall stress–strain response of the cohesive PHFGMC are shown to be in good agreement with those from a finite element analysis for various configurations and loading patterns.